2014
DOI: 10.1039/c4mb00243a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based virtual screening of novel, high-affinity BRD4 inhibitors

Abstract: Bromodomains (BRDs) are a diverse family of evolutionarily conserved protein-interaction modules. Among various members of the bromodomain and extra terminal domain family, BRD4 is found to be an important target for many diseases such as cancer, acute myeloid leukemia, multiple myeloma, Burkitt's lymphoma, etc. Therefore, in this study an attempt has been made to screen compounds from NCI Diversity, Drug Bank and Toslab Databases targeting the Kac binding site of BRD4 using molecular docking, molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In an independent effort, cellular high-throughput screening aiming at the identification of modulators of the ApoA1 pathway was performed [11,[88][89][90]. Later, virtual screening and fragment-based drug discovery have been reported to successfully deliver novel BET inhibitors [91][92][93][94]. Among the most popular methods used in biochemical assays are AlphaScreen ® (PerkinElmer), fluorescence polarization, time-resolved fluorescence resonance energy transfer and the BROMOscan SM technology (DiscoveRx) [95][96][97].…”
Section: Discovery Approachesmentioning
confidence: 99%
“…In an independent effort, cellular high-throughput screening aiming at the identification of modulators of the ApoA1 pathway was performed [11,[88][89][90]. Later, virtual screening and fragment-based drug discovery have been reported to successfully deliver novel BET inhibitors [91][92][93][94]. Among the most popular methods used in biochemical assays are AlphaScreen ® (PerkinElmer), fluorescence polarization, time-resolved fluorescence resonance energy transfer and the BROMOscan SM technology (DiscoveRx) [95][96][97].…”
Section: Discovery Approachesmentioning
confidence: 99%
“…), are the only interaction modules that specifically recognize acetylated lysine residues of histones during transcriptional activation. [14][15][16][17][18] Many of BRDs are regulators of gene transcription such as histone acetyltransferases, components of chromatin remodeling complexes, and methyltransferases. 16,19 Human proteome analysis has revealed that there are eight distinct BRD families, representing 61 different BRDs from 46 separate proteins, although others may still be undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…27 This protein is particularly suitable for this type of calculation, since the ligands bind near its surface and with clear access to the solvent, avoiding steric clashes during the pulling process. It is worth noting that the first BRD4 bromodomain has already been the target of numerous computational studies on ligand binding, using a range of methods such as fragment-based docking, 33 the MM-PBSA/GBSA method combined with steered molecular dynamics (SMD), 34 and free energy techniques, such as umbrella sampling, 35 ABF, 21 and alchemical methods. 11 In this last study, Aldeghi et al computed the binding free energies of several molecules to the BRD4 bromodomain, starting both from the crystal structure complexes and the binding poses obtained after performing protein–ligand rigid docking, and obtained encouraging agreement with experiment.…”
Section: Introductionmentioning
confidence: 99%